Wizualizacja w dawnych polskich materiałach do nauki języka angielskiego - estetyka i funkcjonalność (rekonesans badawczy) = Visualization in the old polish materials for english language learning - aesthetics and functionality (preliminary research) - Kotlarska, Irmina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the undertaken considerations is to identify and describe means of text visualization in English textbooks published before World War II and to determine the role of these elements in the didactic text. Analyzes were subjected to the ways of operating with the convention of recording and the illustrations appearing less frequently in the texts. The bases of the observations were four English language tutorials published in the period 1913-1939.
Keywords: podręczniki do nauki języka angielskiego z I połowy XX wieku; środki wizualizacji; elementy ikoniczne w tekście; teksty dydaktyczne; textbooks for learning English from the first half of the twentieth century; means of visualization; iconic elements in the text; didactic texts